Transition metal-free iminoiodane-mediated amination of activated C-H bonds - Tejo, Ciputra (2016)
Novel transition metal-free-mediated amination of C–H bonds with the use of arylsulfonyliminophenyliodinane (PhI=NSO2Ar) have been developed. The use of iodine(III) compound has shown to be compatible under Brønsted acid and base conditions for the synthesis of unnatural amino ester derivatives and aziridines from 1,3-dicarbonyl compounds, respectively. The amination of cyclic ethers with iminoiodanes was explored subsequently. These cyclic ethers could undergo ring opening and further functionalization with nucleophiles was realized to give the 2-substituted cyclic ether and amino alcohol products under their respective reaction conditions.